2016
DOI: 10.1002/ps.4337
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-based gene silencing through dsRNA injection or ingestion against the African sweet potato weevilCylas puncticollis(Coleoptera: Brentidae)

Abstract: We conclude that the full potential of RNAi in SPW is affected by the presence of nucleases. Therefore, for future application in crop protection, it is necessary constantly to provide new dsRNA and/or protect it against possible degradation in order to obtain a higher RNAi efficacy. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
76
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 45 publications
11
76
0
1
Order By: Relevance
“…The degradation in C. puncticollis gut secretions happens faster than in C. brunneus . Comparing the oral RNAi results presented here and by Prentice et al 38,. we observed that C. brunneus is more sensitive to oral RNAi than C. puncticollis .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The degradation in C. puncticollis gut secretions happens faster than in C. brunneus . Comparing the oral RNAi results presented here and by Prentice et al 38,. we observed that C. brunneus is more sensitive to oral RNAi than C. puncticollis .…”
Section: Discussionsupporting
confidence: 63%
“…we observed that C. brunneus is more sensitive to oral RNAi than C. puncticollis . This could be related to the stronger dsRNA degradation capacity that was observed in C. puncticollis compared to C. brunneus 38.…”
Section: Discussionmentioning
confidence: 98%
“…Similar to the results from previous studies of the cotton boll weevil and the African sweet potato weevil (Baum et al, ; Macedo et al, ; Prentice et al, ), our data show that robust gene silencing can be achieved when naked dsRNAs are delivered through injections, but not through oral ingestion. A recent study in the cotton boll weevil showed that midgut nucleases degraded dsRNA and precluded orally delivered dsRNA from achieving strong RNAi (Almeida Garcia et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…RNA interference has been shown to be effective in inducing gene silencing in the cotton boll weevil Anthonomus grandis (Coleoptera: Curculionidae) and the African sweet potato weevil Cylas puncticollis (Coleoptera: Brentidae) (Gillet et al, ; Macedo et al, ; Prentice et al, ). Interestingly, unlike western corn rootworm, dsRNAs delivered through ingestion were not as effective as those delivered through injections in eliciting strong RNAi responses in either weevil species (Baum et al, ; Macedo et al, ; Prentice et al, ). A recent study in cotton boll weevil showed degradation by midgut nucleases was major cause for the lack of a strong RNAi response following oral delivery of dsRNA (Almeida Garcia et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated significant reduction in the transcript levels of all genes tested 3 days after dsRNA injection, suggesting that SLW adults possess a functional RNAi machinery and systemic RNAi response. Previous studies in weevils Cylas puncticollis and Cylas brunneus reported that injection of dsRNA for the same genes resulted in high lethality . Although gene expression was not evaluated in these previous works, the insect mortality was presumed to be due to gene knockdown.…”
Section: Discussionmentioning
confidence: 99%